Hyperthermia suppresses the biological characteristics and migration of chicken primordial germ cells - Gu, Yuzhou; Wu, Kexin; Niu, Bowen; Wang, Zhiting; Jie, Yuchen; Fan, Zixuan; Li, Junying; Sun, Congjiao; Hou, Zhuo-Cheng; Shao, Li-Wa (Frontiers in Genome Editing, 2025)
Primordial germ cells (PGCs) play a crucial role in transmitting genetic information to the next-generation. In chickens, genetically edited PGCs can be propagated in vitro and subsequently transplanted into recipient embryos to produce offspring with desired genetic traits. However, during early embryogenesis, the effects of external conditions on PGC migration through the vascular system to the gonads have yet to be explored, which may affect the efficiency of preparing gene-edited chickens. In this study, we investigated the effects of hyperthermia on the biological characteristics and migration of chicken PGCs. A gonad-derived PGC line of White Leghorn (WLH) chicken was established and verified through PAS staining and immunofluorescence of PGC-specific proteins. To visually observe PGC migration in vivo, GFP-positive PGCs were prepared and locations of chimeras were validated. Cell viability, glycogen granule contents, and mRNA expression levels of pluripotency markers (NANOG and POUV), germ cell-specific markers (DAZL and CVH), and telomerase reverse transcriptase (TERT) were reduced in PGCs cultured under high temperatures (43°C for 12, 24, and 48 h). After the heat treatment of donor PGCs (43°C) or recipient embryos (39.5°C), GFP-positive PGCs in gonads were rarely observed. Taken together, our results underscore the negative effects of hyperthermia on the biological characteristics and migration of chicken PGCs, which provides valuable insights for the implementation of PGC-based gene editing techniques in chickens.